INOVASI PEMANFAATAN EKSTRAK ALGA HIJAU Ulva sp dari PANTAI LUK,SUMBAWA SEBAGAI KANDIDAT ANTIBAKTERI TERHADAP Salmonella thypi dan Staphylococcus aureus - Adha Ardinata, Rian; Manguntungi, Baso (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2020)
Indonesia is a maritime country that has rich marine resourcesoverflow. One of them is algae, which are distributed in almost all watersIndonesia is included in the Luk sea area, Sumbawa. Wrong type of potential algaehas the most content of primary and secondary metabolite compounds is algaegreen. This research was conducted to determine the antibacterial activity of the extractrough green algae from Luk beach. This research includes identifying green algaebased on morphological characteristics, followed by extracting green algae usingThe maceration method using distilled water was previously carried out in three preparationssamples namely drying (27 ° C), heating (70-80 ° C) and cooling (-10 ° C),each tested with a concentration of 20%, 40%, 60%, 80% and 100% then testedin vitro against Salmonella thypi and Staphylococcus aureus. TestingGreen algae antibacterial shows a different zone of inhibition in each type of extractionand concentrations of both pathogenic bacteria. The greatest inhibition zone against s.thypi isby using the extraction method with a concentration of 60% drying and method100% heating, while the greatest against s.aureusi is by usingextraction method heating concentration 80%.